2015
DOI: 10.1155/2015/481615
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Gasification of Coconut Shell with CO2and KOH: Effects of Temperature, Chemical Loading, and Introduced Carbonization Step on the Properties of Syngas and Porous Carbon Product

Abstract: Effect of KOH, reaction temperature and time, and introduced carbonization step on the amount and composition of syngas as well as porous properties of the carbon products for CO2gasification of coconut shell at low temperatures (300–700°C) was investigated. Results showed that the presence of potassium hydroxide and gasification temperature had a significant effect on the amount and composition of syngas product and facilitated the rate of hydrogen and carbon monoxide formation. It was also found that carboni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…Because the surface properties of the carbon precursors are associated with an oxidation-reduction reaction during the activation process [17,18], an increase in O, which is an electron donor, on the carbon surface will strongly affect the pore development of the carbon matrix. Kopyscinski et al [19] and Quyn et al [20] have both proposed that C-O-K bound during the alkali-metal (i.e., K 2 CO 3 ) impregnation is reduced to C-K at the surface of the carbon body, accompanied by the generation of CO. Lee et al [21] and Punsuwan et al [22], who qualitatively and quantitatively measured the gases emitted during the KOH activation of AC, also confirmed that CO is the main syngas (K 2 O + C → 2K + CO at 800-850 • C [17,18]). To more closely investigate these binding properties of the carbon precursors, we deconvoluted the K and O peaks in the XPS spectra (Table 2).…”
Section: Changes In Thermal Stability Of Chemical Agentsmentioning
confidence: 93%
“…Because the surface properties of the carbon precursors are associated with an oxidation-reduction reaction during the activation process [17,18], an increase in O, which is an electron donor, on the carbon surface will strongly affect the pore development of the carbon matrix. Kopyscinski et al [19] and Quyn et al [20] have both proposed that C-O-K bound during the alkali-metal (i.e., K 2 CO 3 ) impregnation is reduced to C-K at the surface of the carbon body, accompanied by the generation of CO. Lee et al [21] and Punsuwan et al [22], who qualitatively and quantitatively measured the gases emitted during the KOH activation of AC, also confirmed that CO is the main syngas (K 2 O + C → 2K + CO at 800-850 • C [17,18]). To more closely investigate these binding properties of the carbon precursors, we deconvoluted the K and O peaks in the XPS spectra (Table 2).…”
Section: Changes In Thermal Stability Of Chemical Agentsmentioning
confidence: 93%
“…It also helps in the determination of interrelationships among response variables, representing their combined effect in any response. This method enables a researcher to conduct an effective study of an experimental process [14][15][16]. The optimization of industrial processes requires some response parameters that indicate the performance of systems to be optimized.…”
Section: Introductionmentioning
confidence: 99%
“…World Energy Agency (International Energy Agency-IEA) showed that at 2030 world energy demand increased by 45%, or an average increases of 1.6% per year and about 80% of the world's energy requirements are provided from fossil fuels that cause instability the price and supply of fossil fuels [1]. In addition, the burning of fossil fuels would produce CO2, SOx, NOx and other pollutants that are the main cause of acid rain and greenhouse gases that poses a threat to the global climate [2].…”
Section: Introductionmentioning
confidence: 99%
“…Biomass is a raw material generated from forests, agriculture and livestock industry that has the potential to reduce emissions on the environment and stabilize energy needs [3]. Biomass is an environmental friendly alternative energy because it contains no sulfur, carbonneutral, and a plentiful material [1]. These alternative fuels are obtained from resources other than petroleum.…”
Section: Introductionmentioning
confidence: 99%